2017
DOI: 10.1039/c7ra09480a
|View full text |Cite
|
Sign up to set email alerts
|

Emerging trends in organotellurolate chemistry derived from platinoids

Abstract: This perspective begins with the discussion of various basic synthetic approaches applied for the synthesis of several organotellurium ligands, their chemistry derived from platinum group metals, and the reactivity difference among them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 191 publications
0
7
0
Order By: Relevance
“…During the last three decades these complexes have attracted more attention, which is centered on the ligand chemistry of seleno- and telluroethers in addition to thioethers (for more recent reviews, see ref. 5). Hieber and John 6 explored already in 1970s the isomerism of [RuCl 2 (CO) 2 (ERR′) 2 ] (E = S, Se, Te; R, R′ = a number of alkyl or aryl groups) by recording the dipole moments, IR spectra, and 1 H NMR spectra of the complexes formed in different reactions.…”
Section: Introductionmentioning
confidence: 99%
“…During the last three decades these complexes have attracted more attention, which is centered on the ligand chemistry of seleno- and telluroethers in addition to thioethers (for more recent reviews, see ref. 5). Hieber and John 6 explored already in 1970s the isomerism of [RuCl 2 (CO) 2 (ERR′) 2 ] (E = S, Se, Te; R, R′ = a number of alkyl or aryl groups) by recording the dipole moments, IR spectra, and 1 H NMR spectra of the complexes formed in different reactions.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Interestingly, unlike organosulfur derivatives, the NMR activity of the nucleus of 125 Te enables chemists to study the organotellurium compounds using 125 Te NMR spectroscopic techniques. Despite this advantageous feature, 16,17 the chemistry of organotellurium compounds has remained neglected for many years, probably owing to the belief that they have malodorous and unstable character, 18 strong reactivity, 19 and air as well as light sensitivity. 19 Though such properties are shown by some of the organotellurium compounds, it is not true for all Te-containing compounds and it is not less interesting at all to explore them in the field of catalyst development.…”
Section: Introductionmentioning
confidence: 99%
“…Also, for C–E (E = Te, Se, S) the bond energies are substantially lower for tellurium. 1,9 Therefore, the formation of several tellurium compounds can result from the Te–Te or Te–C bond cleavage. 10–14…”
Section: Introductionmentioning
confidence: 99%
“…Also, for C-E (E = Te, Se, S) the bond energies are substantially lower for tellurium. 1,9 Therefore, the formation of several tellurium compounds can result from the Te-Te or Te-C bond cleavage. [10][11][12][13][14] Recently, our research group reported the synthesis and structural characterization of exotic pyridyltellurolate clusters, zwitterionic and coordination compounds using bis(2-pyridyl) ditellane (Fig.…”
Section: Introductionmentioning
confidence: 99%